MONKEYPOX: EMERGING CASES - Cid Martínez, Marcela Alejandra (Kuxulkab’, 2022)
Monkeypox, also called monkeypox, is a disease that is transmitted from wild animals to people; the pathogen that produces it is the Monkeypox virus. The first case of contagion in humans occurred in 1970, since then to date cases have been registered mostly in the African continent, which gave rise to the disease, and sporadically in other continents, however, from May to July of the year 2022, the number of emerging cases has increased, drawing the attention of the health authorities, who have proposed strategies for its control and prevention aimed at the world population. The objective of this document, based on a documentary review, is to report in an accurate and timely manner the clinical characteristics of the disease, as well as its epidemiology without neglecting the actions and proposals of the World Health Organization.